Décoder la diaspora de Stuart Hall. Historicité, performativité et performance d’un concept - Christine Chivallon (Diasporas: Circulations, Migrations, Histoire)
This article analyzes “Stuart Hall’s diaspora” using concepts formulated by the sociologist himself. Through the model of “encoding-decoding”, it explores the meanings of the Caribbean diasporic formations and the theoretical positioning of Stuart Hall. The first part adopts a comparative approach on the usages of diaspora within the French and British academic circles, relying on two exemplary texts to demonstrate the hegemony of discursive norms prevalent in each of these spheres. The “diaspora of Stuart Hall” seems to depend on the historicity of codes that witnessed the shift in the post-modern paradigm. The second part is on the margins from which Stuart Hall reconfigured this shift with an “articulation” of his positioning to academic normativity. These margins also bring to light his critical theoretical posture vis-à-vis postmodernism, as well as the unusual expression of his personal motivation that led to the adoption of a discursive approach to diaspora.